Determination of coproporphyrin I and III in human urine using HPLC with fluorescence detection - Kanďár, Roman; Žáková, Pavla; Frölichová, Martina; Štramová, Xenie; Bencová, Soňa (Univerzita Pardubice, 2010)
The determination of selected porphyrins, especially of coproporphyrin I and III is presently the most reliable direct approach to the screening of porphyrias. An HPLC method for the simultaneous measurement of coproporphyrin I and III in urine samples has been developed and evaluated. Separation of coproporphyrin I and III from interfering substances was achieved on reversed phase HPLC with gradient elution and fluorescence detection. Analytical performance of this method is satisfactory for both coproporphyrin I and coproporphyrin III: the intra-assay and inter-assay coefficients of variation were below 10 %. Quantitative recoveries from spiked urine were between 85.0 and 101.1 %. The limit of detection was 3.0 and 2.3 :g l–1, respectively. The preliminary reference ranges of coproporphyrin I and III in a group of donors are 5.0-51.6 :g l–1 88 Kanďár R. et al./Sci. Pap. Univ. Pardubice Ser. A 16 (2010) 87–98(0.59-3.20 :g mmol–1 creatinine) and 14.9-65.4 :g L-1 (0.98-8.21 :g mmol–1 creatinine). The presented method is inexpensive and suitable for screening of porphyrias.
Keywords: porphyrins; HPLC method; coproporphyrin I; coproporphyrin III